(untitled) (Actualizaciones en Sida e Infectología, 2025)
Typhoid and paratyphoid fevers are invasive bacterial diseases caused by Salmonella serovars that affect only humans such as Salmonella Typhi and Salmonella Paratyphi A, B[1] and C. After an incubation period of 6 to 30 days (1 to 3 weeks for typhoid fever and 10 to 15 days for paratyphoid), the disease emerges insidiously with the gradual onset of fever, fatigue, anorexia, headache, malaise and abdominal symptoms. If treatment is delayed or inadequate, it can lead to meningitis, sepsis or intestinal perforation and even death (1). Carrier status may follow acute or mild illness, or even subclinical infection, which will continue to excrete the bacteria after resolution of symptoms. Prior infection provides partial immunity. An increase in antimicrobial resistance is observed in different regions of the world (2). In our country, a decrease in sensitivity to ciprofloxacin in isolates of S. Paratyphi B was determined from 2021 to 2023. No resistant isolates have yet been recorded in cases of S. Typhi. Transmission occurs mainly by the fecal-oral route, through the consumption of food or water contaminated with the feces of a carrier. Chronic carriage plays a role in transmission in non-endemic countries, spreading the pathogen to the environment. Person-to-person transmission, mainly associated with men who have sex with men, has been reported on rare occasions (3). S. typhoidalis can persist in the environment for a prolonged period if control and sanitation conditions are inefficient, generating an environmental niche, a potential source of outbreaks (e.g., from fruit and vegetable crops contaminated with sewage). By 2021, the overall adjusted incidence rate for typhoid and paratyphoid fevers was estimated at 127.77 cases per 100,000 inhabitants and the mortality rate at 1.5. Although the overall trend is downward, the distribution is very uneven, with the highest incidences in South Asia (379.64), Oceania (293.05), Southeast Asia (151.55), West Sub-Saharan Africa (109.27) and East Africa (117.84), where these diseases are endemic, while in countries with a high socio-demographic index, incidence rates were calculated at 1.54 and mortality rates at 0.01 (1). In 2018, WHO recommended prioritizing the introduction of typhoid vaccine in countries with the highest burden of typhoid fever or antimicrobial-resistant S. Typhi. It also recommended vaccination for travelers to endemic areas and its use for outbreak control, although data on its use are still very limited (4). In non-endemic regions, timely diagnosis and treatment and epidemiological surveillance are the measures to prevent transmission, within the framework of the population’s access to adequate water, hygiene and sanitation conditions. The increasing flow of travelers to and from endemic areas and rising temperatures have increased the risk of imported typhoidal Salmonella infections in non-endemic countries. In Argentina, cases of S. Typhi and S. Paratyphi were historically sporadic and associated with travel to endemic regions. However, two situations have been recorded in recent years that show the potential risk of dissemination under certain conditions. On the one hand, in 2018, the emergency of cases of the serovar S. Paratyphi B was recorded in Salta. About 130 cases were reported in the province that year, reaching an average of about 2,000 cases reported between 2021 and 2023. After several years of research, the province implemented the strategy called “Cordón Sanitario Subcuenca Río Arias-Arenales” (Arias-Arenales River sub-basin sanitary zone), based on intensified multidisciplinary and interinstitutional epidemiological surveillance of events potentially associated with the river water and linked to the potentially contaminating sewage treatment plant. From 2024 onwards, the number of registered cases decreased significantly and in 2025 sporadic cases are registered in a much lower number than usual (5). The other situation to be highlighted is the cluster of typhoid fever cases identified in March 2025 in a district of the urban area of Buenos Aires. The immediate investigation revealed that all the patients lived in two adjacent buildings, and the common source of infection was identified as drinking water from well water, confirming the epidemiological relationship of the isolates by genomic sequencing at the National Reference Laboratory. The actions of providing safe water, verification and remediation of the sanitary infrastructure of the buildings made it possible to control the common-source outbreak in which 47 suspected cases were detected, 27 of which were laboratory-confirmed between March and May (5). This outbreak made it possible to sensitize health personnel to detect cases and to optimize the care and diagnosis circuit in health facilities within the affected area. Given that the risk of sporadic cases or limited outbreaks from chronic carriers is sustained, surveillance and follow-up of cases and contacts continues to this day. Both situations highlight the importance of having a surveillance system that is sensitive to clinical-epidemiological suspicion and capable of guiding investigation and control measures in a timely manner. Typhoid and paratyphoid fevers can be difficult to distinguish from other pathologies with similar clinical presentation and may be underdiagnosed. Therefore, it is important to have access to specific microbiological diagnosis based on blood and stool cultures, both for the implementation of appropriate treatment and for effective case reporting, allowing timely epidemiological field investigation and consequent control actions. It is also essential to highlight the multisectoral and interdisciplinary actions needed to ensure access to safe water, sanitation and hygiene as pillars not only of foodborne disease prevention, but also of human dignity and well-being (6). [1] SPB can also be found in animals since this serovar can be differentiated into two pathovars, systemic or enteric.